FORMULATION AND EVALUATION OF IMMEDIATE RELEASE TABLET OF ROSUVASTATIN CALCIUM BY LIQUISOLID COMPACT TECHNIQUE - Suthar, Manishkumar J.; Raval, Mr. Anil; Pate, Dr. Ravi R.; . Patel, Dr. L. D (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The in-vitro dissolution property of poorly water soluble Rosuvastatin calcium was improved by exploring the potential of Liquisolid compact technique. In this technique, liquid medications of water-insoluble drugs in liquid vehicles (non-volatile solvents) can be converted into acceptably flowing and compressible powders. Different liquisolid compacts were prepared using the required quantities of powder and liquid ingredients to produce acceptably flowable and compressible admixture. To improve aqueous solubility as well as poor dissolution rate of Rosuvastatin calcium, Propylene glycol was selected as non- volatile Solvent, Anhydrous dibasic calcium phosphate and Syloid 244FP was selected as carrier and coating material respectively. The formulated liquisolid system were evaluated for their various pre-compression and post-compression parameters. From the results, it was found that solubility and drug release increased with lower drug concentration. Optimized formulation LS1 showed satisfactory results of cumulative percentage release (88.98±0.80% at 30 min., 98.27±2.0% at 60 min.). The selected formulation (LS1) was found to be stable at 40 ± 0.5 °C and 75 ± 5% RH during the test period of 1 month. From this study it concludes that, the liquisolid technique is a promising technique for improvement of dissolution property of poorly water-soluble drugs and formulating immediate release solid dosage forms